Research on the Coordination and Matching of Cylinder Head Gasket Strength and Sealing Performance. Issue 2 (April 2021) - Wang, Long; Zuo, Zhengxing; Cheng, Ying; Zhu, Xinran
Abstract: In this paper, the cylinder head gasket of a certain type of diesel engine is taken as the research object. Under the condition of changing the mechanical load parameters, the changing trend of the strength and sealing performance of the cylinder head gasket is analyzed, and then its reliability and durability are evaluated. Through the analysis, we can see that the changing trend of the strength and sealing performance of the cylinder head gasket is the opposite. Therefore, in this paper, the fatigue life and sealing performance of the cylinder head gasket are regarded as factors with equal weight, and the total coordination coefficient is introduced to measure the change of the strength and sealing performance of the cylinder head gasket after changing the explosion pressure and bolt preload, the best loading scheme is selected.